Assessment of image quality of a radiotherapy-specific hardware solution for PET/MRI in head and neck cancer patients. Issue 3 (September 2018) - Winter, René M.; Leibfarth, Sara; Schmidt, Holger; Zwirner, Kerstin; Mönnich, David; Welz, Stefan; Schwenzer, Nina F.; la Fougère, Christian; Nikolaou, Konstantin; Gatidis, Sergios; Zips, Daniel; Thorwarth, Daniela
Abstract: Background and purpose: Functional PET/MRI has great potential to improve radiotherapy planning (RTP). However, data integration requires imaging with radiotherapy-specific patient positioning. Here, we investigated the feasibility and image quality of radiotherapy-customized PET/MRI in head-and-neck cancer (HNC) patients using a dedicated hardware setup. Material and methods: Ten HNC patients were examined with simultaneous PET/MRI before treatment, with radiotherapy and diagnostic scan setup, respectively. We tested feasibility of radiotherapy-specific patient positioning and compared the image quality between both setups by pairwise image analysis of 18 F-FDG-PET, T1/T2-weighted and diffusion-weighted MRI. For image quality assessment, similarity measures including average symmetric surface distance (ASSD) of PET and MR-based tumor contours, MR signal-to-noise ratio (SNR) and mean apparent diffusion coefficient (ADC) value were used. Results: PET/MRI in radiotherapy position was feasible – all patients were successfully examined. ASSD (median/range) of PET and MR contours was 0.6 (0.4–1.2) and 0.9 (0.5–1.3) mm, respectively. For T2-weighted MRI, a reduced SNR of −26.2% (−39.0–−11.7) was observed with radiotherapy setup. No significant difference in mean ADC was found. Conclusions: Simultaneous PET/MRI in HNC patients using radiotherapy positioning aids is clinically feasible. Though SNR was reduced, the image quality obtained with a radiotherapy setup meets RTP requirements and the data can thus be used for personalized RTP.